Original articleOpioid agonist – tachykinin antagonist as a new analgesic with adjuvant anticancer properties - Matalińska, Joanna; Skurzak, Henryk; Markowicz, Sergiusz; Lesniak, Anna; Sacharczuk, Mariusz; Molnar, Gabriella; Varga, Eva; Lipkowski, Andrzej W. (Folia Neuropathologica, 2013)
Opiate analgesics like morphine or fentanyl are the most widely used medicines for relieving severe acute or chronic pain, including cancer pain. Unfortunately, chronic pain treatment is associated with fast development of tolerance that creates the need to escalate the treatment doses. In addition, opiates may stimulate progression of cancer. Therefore, a new type of effective analgesic especially designed for chronic cancer pain treatment is needed. In this paper, a new opioid peptide analogue has been described as a new analgesic. The compound is characterized by very high agonist affinities to MOR and also high, but ten times lower affinity to DOR. Affinity to hNK1 as an antagonist is on the level of C-terminal hexapeptide fragment analogue of Substance P. The compound expressed reasonable antiproliferative properties toward various cancer cells. Interestingly, the peptide did not interfere with the proliferation of fibroblasts. Therefore, the compound should be considered as a new analgesic for treatment of cancer-related pains with adjuvant anticancer properties which may support cancer treatments.